A naturalized philosophy for research into the administration of educational organizations : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Philosophy of Education at Massey University - Clark, John Andrew; Clark, John Andrew (Massey University, 1995)
After setting out in detail the social-historical context of the theory debate in educational administration and the philosophical elements of the four traditions of inquiry in this field (logical positivism, phenomenology, critical theory, naturalism) along with a consideration of the emerging lines of criticism against naturalism, the central thrust of the thesis is to set out the main features of a naturalized philosophy upon which research into the administration of educational organizations could be based. The notion of naturalized philosophy is discussed, followed by a working out of a naturalized account of the basic ontological, epistemological and axiological assumptions. What is attempted is the construction of a systematic philosophy which seeks to unify these primary branches into a coherent whole tied together by the principles of naturalism. The implications of naturalized philosophy for research into the administration of educational organizations is also examined.
Keywords: Naturalism; Educational planning